Strict compliance of documents in Letters of Credit (LCs) transaction: A new dimension - Che Hashim, R. (2007)
The issue of strict compliance of documents in LCs is a never ending story. It started with the narrow approach that the documents tendered by the seller should strictly comply with buyer's requirement under the LCs. Under this approach, the doctrine of strict compliance must be followed strictly to the extent that the documents must not contain any discrepancies, even minor typographical errors which do not really affect the underlying contract. Minor discrepancies such as wrongly spelt name of a beneficiary, incorrect description of the goods sold, wrong measurement of the quantity of the goods were considered as non-compliance which later served as sufficient grounds for the bank to reject the seller's presentation of documents. As pointed out by Lord Sumner in Equitable Trust v. Dawson Pcrtners,' 'There is no room for the documents which are almost the same or which will do just as well.' This statement denotes that the documents should strictly comply with the terms of the credit and any documents which contain discrepancies should be rejected. Thus, compliance of documents ascertains the success of the LCs transaction. However today, the approach taken by judges seems to be much broader and is open to a more liberal interpretation. This paper discusses the issues of standard of compliance of documents required under the LCs transaction. It also examines whether the literal approach of strict compliance as highlighted by Lord Sumner is still favourable. In relation to this, discussion will be based on case law where the established legal principles from relevant decided cases will be explored. Focus also will be emphasized on other related issues to the compliance of the documents such as provisions under tne Uniform Custom and Practice for Documentary Credit 500.